Evaluation of levels of some heavy metals in marine environment, southern Iraq - Saleh, Salah M.; Abdulnabi, Zuhair A.; Mizhir, Alaa A.; Hantoush, Abbas A.; Hassan, Wesal F.; Al-Khion, Dhafar Dh. (Mesopotamian Journal of Marine Sciences, 2021)
Some toxic and essential heavy metals have been evaluated at five stations of the marine water region of Basrah governorate, southern Iraq. Eight of different elements (Pb, Zn, Ni, Mn, Fe, Cu, Cr and Cd) were measured at five stations from various regions these elements were collected by using water sampler at depth 20-25 cm in low tide at summer season in 2016. They have been analyzed using flame-atomic absorption spectrophotometer. The results of all measurements of heavy metals indicated the dominance zinc more than the other elements at St. 1 and St. 4 ranged from 0.144 to 0.193 mg/l, respectively. St. 2 and St. 5 exhibited the dominance of lead in the range between 0.164 and 0.253 mg/l, respectively. While, St. 3 showed the highest concentration of nickel compared with the other elements (0.190 mg/l). Standard deviation was calculated for all elements measured and were in the ranged or(0.008-0.049).